IMPLEMENTASI KURIKULUM 2013 PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SD MUHAMMADIYAH TERPADU PONOROGO - Nuraini Nuraini; M. Fata Muhtarima (Postgraduate Program Magister Pendidikan Agama Islam, 2016)
Curriculum plays a very important role in realizing the generation of reliable, creative, Innovative and personal responsibility. Therefore, the curriculum must always be prepared and perfected in accordance with the times. Associated with changes in the curriculum, the various parties to analyze and see the need for a competency-based curriculum implemented at once a character-based (competency and character-based curriculum), which can provide students with a wide range of attitudes and capabilities in accordance with the demands of the times and the demands of technology. Character and competency based curriculum is expected to solve the problems of the nation, especially in the field of pedidikan to prepare learners through planning, implementation and evaluation of the education system in an effective, efficient and useful. Curriculum change from time to time regarding structural change and conceptual change and now we are also introduced to the new curriculum is the curriculum applied by the government in 2013 and was passed by Parliament. According to Muhammad Nuh curriculum 2013 is designed as an effort to prepare the next generation of Indonesia in 2045 is exactly 100 years of Indonesian independence, while utilizing the productive age population numbers are very abundant in order to become a demographic bonus and not a demographic disaster. Character education in the curriculum in 2013 aimed at improving the quality of the process and outcomes of education that leads to the formation of character and noble character of learners as a whole, integrated, and balanced in accordance with competency standards in each educational unit. Through the implementation of competency-based curriculum in 2013 at the same time with a character-based thematic and contextual approach is expected that learners are able to independently increase and using the knowledge, study and internalize and personalize the character values and noble character so manifest in everyday behavior.